Knowledge, Attitude, and Practice (KAP) Survey toward Skin Cancer among Ecuadorian Population - Victor H. Pinos-León; César Sandoval; Franklin Cabrera; Esmeraldas Terán; Ana Garnica; Ana Kellendonk; Mery Alvear; Carla Rosero; Lorena Vaca; Jorge Bonifaz; Anita Buestán; Claudia Armas; et al. (Dermatology Research and Practice)
Background. Skin cancer is one of the most common cancers, and melanoma is a highly preventable cancer. In Ecuador, few studies have evaluated the awareness levels of the population about the disease. For this reason, the objective of this study was to measure the level of knowledge, attitudes, and practices regarding skin cancer and its determining factors. Methods. A cross-sectional analysis using an online self-assessment questionnaire containing 40 questions was delivered. A total of 537 participants were included in this study. Knowledge, attitude, and practice scores were assigned to each participant based on the number of correct or appropriate responses. Logistic regression analysis was used to calculate crude and adjusted odds ratios. Results. In total, 75% of participants referenced knowledge of the harmful effects related to noncontrolled solar exposure. Concerning sunscreen, 76.7% knew the reason for using it. The female group was 1.68 times more likely to get a higher score than the male group, and the groups between 61–70 and 71–80 years were 0.30 and 0.17 times less likely to get a higher score compared with the less than 20-years-old group, respectively. Conclusions. The findings of this study indicate the requirement to increase the population’s knowledge about skin cancer and possible protection measures. For this reason, the prevention and health promotion programs at a national level from primary healthcare centers are recommended. Due to the limitation of the representativeness of the sample, the use of more studies among Ecuadorian residents of the low socioeconomic level and replication in different provinces of Ecuador is justified.